The Transformation of the Principle of Good Faith in Digital Agreements: A Civil Law Analysis of Consumer Protection in Electronic Contracts - Fadhil Hayan Mochammad (Golden Ratio of Law and Social Policy Review, 2026)
This study examines the transformation of the principle of good faith in digital agreements within a civil law framework, focusing specifically on consumer protection in electronic contracts. The research aims to analyze how technological developments, platform-based contracting, and data-driven business models have reshaped the doctrinal meaning and operational function of good faith in contemporary digital markets. Employing a qualitative research design based on systematic literature review and doctrinal analysis, the study synthesizes recent academic scholarship, regulatory developments, and legal interpretations concerning electronic contracts, transparency obligations, unfair terms, and digital content regulation. The findings reveal that good faith has evolved from a predominantly interpretative and corrective principle into a broader governance standard encompassing transparency-based fairness, protection of reasonable consumer expectations, control of unilateral modification clauses, and accountability in algorithmic decision-making. The study further identifies a growing convergence between contract law, consumer protection law, and data protection regulation, indicating that good faith increasingly functions as a connective normative principle across digital regulatory regimes. The research concludes that sustainable digital contract governance requires reconceptualizing good faith as a structural fairness standard capable of addressing informational and technological asymmetries in electronic commerce.